An Evaluation of Practitioner's Experience of Service Users Seeking Community Detoxification from Benzodiazepines. Issue 3 (27th May 2018) - Wall, Marianne; Lambert, Sharon; Horan, Aidan
ABSTRACT: A recent report in Ireland identified that two-thirds of poisoning deaths involved poly drug use with an average of four different drugs involved. Of these, benzodiazepines were the most common drug group involved. Concern has been expressed regarding high levels of benzodiazepine prescriptions globally. Community-based detoxification programs are required, but detoxification is complex with associated high risks, such as overdose. This study utilized a survey to gather the experiences of a range of drug workers in addiction settings in the southern region of Ireland who are tasked with the management of supporting service users who wish to detoxify from benzodiazepines. The purpose of this study is to identify the issues highlighted in the data and consequently inform policy development, service delivery, future training, and pathways to support service users (SUs). Findings indicate that, while practitioners had high levels of confidence in managing community-based detoxes, levels of knowledge of schedules, contraindications, access to support, and appropriate referral pathways were limited. Barriers to supporting detoxes emerged, emphasizing the importance of multidisciplinary and interagency care planning. Changing trends in drug use led participants to indicate a need for pharmacology training and development of specific local protocols.